Prevalence of sexual violence and associated factors among women attending antenatal care in Debre Markos at public health institutions in north-west Ethiopia, 2021 - Abegaz, Marta Yimam; Muche, Haymanot Alem; Aynalem, Getie Lake; Anteneh, Tazeb Alemu; Tibebu, Nebyu Solomon; Gedef, Getachew Muluye; Mengstie, Aregash Sitot (Frontiers in Global Women's Health, 2023)
Background Sexual violence refers to being forced to perform any unwanted sexual act. Due to the negative effects on both the mother and the fetus, sexual assault during pregnancy is a public health concern. Knowing the prevalence of sexual violence during pregnancy helps policymakers understand the extent of the problem and can be considered the first step toward implementing interventions for prevention and treatment. This study was done to determine the prevalence of sexual violence and its associated factors during pregnancy in public hospitals in Debre Markos. Methods An institution-based cross-sectional study was conducted among 306 pregnant women in Debre Markos, north west Ethiopia from May 1 to June 30, 2021, 2021. A systematic random sampling procedure was used to select study participants. Data were collected using a structured and interviewer-administered questionnaire, and a pre-test was done. Both bi-variable and multivariable logistic regression analyses were undertaken to identify significantly associated variables with sexual violence. The adjusted odds ratio (AOR) with its 95% confidence interval (CI) at a p-value of ≤ 0.05 was used to claim statistical association. Results There were 304 interviewed respondents with a response rate of 99.3%. In this study, the overall prevalence of sexual violence among pregnant mothers during the current pregnancy was 19.4%. A husband who had no formal education AOR = 3.48; 95% CI: 1.06, 11.39, pregnant mothers who had no formal education AOR = 6.1; 95% CI: 1.50–18.11, pregnant mothers who had secondary education AOR = 2.80, 95% CI: 1.15, 6.81, being a housewife AOR = 3.87, 95 CI:1.21, 12.37, and being a governmental employee AOR = 4.49, 95% CI: 1.22, 16.40 were factors associated with sexual violence at the value of p ≤ 0.05. Conclusions and recommendations In this study, approximately one-fifth of the study participants experienced sexual violence during their current pregnancy. To reduce this, interventions should focus on the education of women as well as their partner about violence against women and on initiatives to economically empower women.